Faktor-faktor yang mempengaruhi niat pengguna islam memilih ubat-ubatan halal - Azmawida, Abdullah (2015)
Today, Muslim population and the halal industry in Malaysia and worldwide are rising rapidly. The halal industry is continuously being debated and discussed as significant issues. Hence, its development convey benefits not only to Muslims but also to the entire global community. Halal food industry and the Islamic finance industry are commonly discussed and researched, however the halal pharmaceutical industry and its specific halal medicine are not being exposed broadly to the world community. Therefore, the awareness about the importance of choosing halal medicines among societies are still low. This study aims to examine factors influencing consumers’ intention to choose halal medicines. Furthermore, it attempts to examine the influence of attitudes, family and friends, and knowledge on consumers’ intention to choose halal medicines. In addition, the Theory of Planned Behavior was used as an underpinning theory to explain the studied variables. The study was conducted in UUM (Universiti Utara Malaysia), in which a total of 430 questionnaires were distributed to visitors and UUM communities. The findings of this study contribute to the existing literature by highlighting the significant influence of attitudes, family and friends, and knowledge on consumers’ intention to choose halal medicines. A general discussion and recommendations from the current findings are provided